Keefektifan Metode Everyone is Teacher Here pada Materi Operasi Hitung Pecahan Kelas 4 Sekolah Dasar - Zakaria, Akhiudin (Universitas Sebelas Maret, 2020)
This research was motivated by the low learning outcomes of fractional operations in grade 4 SDIT Buah Hati. The cause of the problem is the use of conventional learning methods. This type of research is quantitative. Samples were taken randomly without regard to the existing strata in the population. The samples in this study were students in class 4B with a total of 30 students as the experimental class and students in class 4A with a total of 30 students as the control class using purpos4e random sampling technique. The research design used a pretest-posttest control group design. The results of the calculation show that the average value of the experimental class is 85.87 while the average value of the control class is 74.27. For the results of the t-test calculation with dk = 58 and =5%, it is obtained that t_hitung 3,993 and t_table 1,671 So, the value of t_count>t_table, then H0 is rejected. After analyzing the hypothesis, it was concluded that the use of the everyone is teacher here method could improve the learning outcomes of fractional arithmetic operations for 4th grade students of SDIT Buah Hati.